2013
DOI: 10.5455/medarh.2013.67.120-123
|View full text |Cite
|
Sign up to set email alerts
|

Predilection Role Diabetes Mellitus and Dyslipidemia in the Onset of Ischemic Stroke

Abstract: 4Primary Health Care Center Ilijas, Bosnia and Herzegovina 5 I ntroduction: Stroke is the third leading cause of mortality, disability and dementia, but leading cause of epileptic manifestations in the elderly. Diabetes mellitus as permanently elevated blood glucose, often accompanied by dyslipidemia, is among the leading causes of atherosclerotic alteration in blood vessels and is also increasing in the world. Goal: To determine the existence and predilection of diabetes mellitus and dyslipidemia, in the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 6 publications
2
19
3
3
Order By: Relevance
“…Literature review showed hypertension as the major risk factor for stroke worldwide. 25,26 We found dyslipidemia as the major risk factor than hypertension for ischemic stroke being present in 79% of the cohort, higher than reported. 25,26 This is attributed to the life style changes and consumption of fatty foods (Biryani, ice creams, fast foods and meat products) in these region.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Literature review showed hypertension as the major risk factor for stroke worldwide. 25,26 We found dyslipidemia as the major risk factor than hypertension for ischemic stroke being present in 79% of the cohort, higher than reported. 25,26 This is attributed to the life style changes and consumption of fatty foods (Biryani, ice creams, fast foods and meat products) in these region.…”
Section: Discussioncontrasting
confidence: 46%
“…25,26 We found dyslipidemia as the major risk factor than hypertension for ischemic stroke being present in 79% of the cohort, higher than reported. 25,26 This is attributed to the life style changes and consumption of fatty foods (Biryani, ice creams, fast foods and meat products) in these region. Plasma lipids and lipoproteins have an influence on the risk of cerebral infarction, but the relationships between dyslipidemia and stroke have not been consistently elucidated.…”
Section: Discussioncontrasting
confidence: 46%
“…Išeminiu insultu sergantiems ligoniams CD nulemia blogą prognozę po trombolizės, o ankstyva poinsultinė glikemija yra susijusi su potrombolizinių simptominių ICK padaugėjimu [28]. Laiku diagnozavus ir gydant CD, galima kontroliuoti kraujagyslių aterosklerozinius pokyčius ir išvengti išeminio insulto [29]. Nagrinėjamos diabetinės ketoacidozės neurologinės komplikacijos vaikams: diabetinė ketoacidozė gali komplikuotis galvos smegenų edema ir išeminiu insultu [30].…”
Section: Rezultatų Aptarimasunclassified
“…Değiştirilebilen risk faktörlerinin ortaya konulması serebrovasküler hastalıkların tedavi yaklaşımları açısından da önem kazanmaktadır (1).…”
Section: Introductionunclassified
“…Diabetes mellitus (DM), anormal glukoz metabolizmasının yol açtığı, beraberinde lipid ve protein metabolizmasında da değişikliklere neden olabilen kronik hiperglisemi ile karakterize metabolik bir bozukluktur (1). Hiperglisemi belirtileri gösteren olgularda açlık kan glukoz düzeylerinin ≥126 mg/dL (7.0 mmol) olması, Hemoglobin A1C'nin ≥%6.5 olması veya rastgele ölçülen kan glukoz düzeylerinin ≥200 mg/dL (11.1 mmol/l) olması DM tanısı için gereklidir (2).…”
Section: Introductionunclassified